2014
DOI: 10.1159/000365726
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Diversity of Multidrug-Resistant Pseudomonas aeruginosa Isolates from Bloodstream Infections Recovered in the Hospitals of Belo Horizonte, Brazil

Abstract: Background: Pseudomonas aeruginosa commonly causes nosocomial bloodstream infections and the emergence of a variety of β-lactamases (BLs) is worrying. In 5 hospitals in Belo Horizonte, Brazil, the presence of phenotypes encoding BL genes was established and the genetic diversity of the P. aeruginosa strains recovered from bloodstream infections was analyzed. Materials and Methods: The isolates were investigated using a disk diffusion (DD) method and the Etest®, for encoding metallo-β-lactamases (MBLs), oxacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
(59 reference statements)
1
11
1
Order By: Relevance
“…Amongst MBL-positive isolates in the current study, 3 contained bla VIM-2 , which has been found worldwide, e.g. in Brazil, Norway and Poland [ [24,41,43]; Empel and Gniadkowski, unpubl. results].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Amongst MBL-positive isolates in the current study, 3 contained bla VIM-2 , which has been found worldwide, e.g. in Brazil, Norway and Poland [ [24,41,43]; Empel and Gniadkowski, unpubl. results].…”
Section: Discussionmentioning
confidence: 69%
“…results]. None of the tested isolates were positive for bla SPM-1 , which appears to be restricted to Brazil [24,43]. Acquired MBLs are emerging and should be carefully monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with a larger number of isolates are necessary to obtain a better picture of the circulating clones at Mulago Hospital. Other researchers who used Rep-PCR genotyping also reported a high level of genetic diversity among P. aeruginosa isolated from a hospital in Belo Horizonte, Brazil [22]. Moreover, a nonclonal epidemic population structure of P. aeruginosa , supported by lack of evidence for a widespread cystic fibrosis transmissible clone, has been reported [27].…”
Section: Discussionmentioning
confidence: 98%
“…up-regulated efflux pumps or outer membrane impermeability [21] outlined above. Indeed, carbapenem resistant P. aeruginosa and Acinetobacter strains that are resistant to aztreonam have been reported by researchers worldwide [22]. Taken together, there is surprisingly high level of aztreonam resistance in P. aeruginosa isolated from hospital environments [23].…”
Section: Discussionmentioning
confidence: 99%
“…Emergence of distinct clonal populations of P. aeruginosa even within hospitals of the same city has been shown in recent studies [30] , while both cross-transmission and treatment failures are major problems that should be curbed to reduce the generation and spread of P. aeruginosa infections [31] . Also, very little clinical information was collected on the patients infected with P. aeruginosa.…”
Section: Resistance To 3 Indicated Classes (N = 116)mentioning
confidence: 99%